The effect of health-care privatisation on the quality of care - Goodair, B; Reeves, A (Elsevier, 2024)
Over the past 40 years, many health-care systems that were once publicly owned or financed have moved towards privatising their services, primarily through outsourcing to the private sector. But what has the impact been of privatisation on the quality of care? A key aim of this transition is to improve quality of care through increased market competition along with the benefits of a more flexible and patient-centred private sector. However, concerns have been raised that these reforms could result in worse care, in part because it is easier to reduce costs than increase quality of health care. Many of these reforms took place decades ago and there have been numerous studies that have examined their effects on the quality of care received by patients. We reviewed this literature, focusing on the effects of outsourcing health-care services in high-income countries. We found that hospitals converting from public to private ownership status tended to make higher profits than public hospitals that do not convert, primarily through the selective intake of patients and reductions to staff numbers. We also found that aggregate increases in privatisation frequently corresponded with worse health outcomes for patients. Very few studies evaluated this important reform and there are many gaps in the literature. However, based on the evidence available, our Review provides evidence that challenges the justifications for health-care privatisation and concludes that the scientific support for further privatisation of health-care services is weak.